Crawford Automation A Guided Application of Structured Problem Solving - Thomson, Stephen; Hollis, Kevin; Turnbull, Laurie (Open textbook library., 2023)
This is a multimedia-enabled case in which students will be guided, by an industry expert, to apply structured problem-solving that addresses a typical supply chain problem, missing parts. What first appears as the issue may be a symptom of a root cause(s). The case utilizes videos, data files for analytics, audio recording, and videogame-style exercises to find the missing box of parts. The case is a collaboration between the Conestoga Centre for Supply Chain Innovation and ATS Automation and utilizes the ATS Business Model (ABM) approach to identifying and solving root causes. The case can be used in any Continuous Improvement course or program for either Business or Engineering students.